2012
DOI: 10.1097/mlr.0b013e318245a558
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Costs of Co-occurring Traumatic Brain Injury With and Without Psychiatric Disturbance and Pain Among Afghanistan and Iraq War Veteran VA Users

Abstract: The vast majority of VHA patients diagnosed with TBI also have a diagnosed mental disorder and more than half have both PTSD and pain. Patients with these comorbidities incur substantial medical costs and represent a target population for future research aimed at improving health care efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
176
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 294 publications
(187 citation statements)
references
References 23 publications
9
176
2
Order By: Relevance
“…This would agree with findings in other anxiety disorders. However, the majority of patients seen clinically and recruited into the study had both PTSD and mTBI, which is consistent with the observations of other investigators (Carlson et al, 2011;Taylor et al, 2012). Thus, the question is whether combat Veterans with PTSD (most with mTBI as well, but some with PTSD-only) will show deficits in error monitoring as indexed by the ERN.…”
Section: Introductionsupporting
confidence: 83%
“…This would agree with findings in other anxiety disorders. However, the majority of patients seen clinically and recruited into the study had both PTSD and mTBI, which is consistent with the observations of other investigators (Carlson et al, 2011;Taylor et al, 2012). Thus, the question is whether combat Veterans with PTSD (most with mTBI as well, but some with PTSD-only) will show deficits in error monitoring as indexed by the ERN.…”
Section: Introductionsupporting
confidence: 83%
“…Likewise, our data in patients with spasticity concurs with previous studies that reported prevalence of pain in stroke to be 19-75%, [26][27][28] 53% in MS, 29 64.9% in SCI 30 and 70% in brain injured patients. 31 The Cochrane Collaboration Systematic Review 32 reported a decrease in shoulder pain after injection of BoNTA; but in contrast, our study provides data on the prevalence of pain at any site in the body (not limited to shoulder pain) in patients experiencing spasticity due to various etiologies. Thus, our study results provide unique data to help understand patient perception of pain within the context of the experience of spasticity.…”
Section: Discussionmentioning
confidence: 63%
“…This carries an inherent risk of false positives and false negatives, as well as sampling differences [16]. The gold standard for TBI diagnosis is a clinical interview and evaluation with a specialist (as opposed to self-report surveys, imaging, or laboratory testing) because of the difficulty obtaining accurate information on TBI history through brief self-report measures and no defined physiologic or biologic marker [7]. Self-report measures may overestimate the rate of TBI compared with clinical assessment, just as they have been found to overestimate the rate of PTSD relative to gold standard interviews [17][18].…”
Section: Discussionmentioning
confidence: 99%
“…A 2009 national sample of all OIF/OEF Veterans who received VA care during that year revealed that 6.7 percent had been diagnosed with TBI [7]. In this TBI group, 89 percent had a concomitant mental health disorder, with the most frequent diagnosis being PTSD (73%); 70 percent had a concomitant pain disorder; and 54 percent had both PTSD and pain (the polytrauma triad).…”
Section: Introductionmentioning
confidence: 99%